Game-Theoretical Resource Model of Balanced Technological Development - Polumiienko, S.K.; Gorda, S.E. (Математичне моделювання в економіці, 2017)
This article proposes a game-theoretical resource approach to the modeling of sustainable development processes. Initial system is considered as an aggregate of various resources and participants consuming and creating these resources to meet their needs or interests. The system participants are not divided by economic, environmental and social subsystems. Their strategies or technologies are aimed at deriving income from the production and consumption of resources, which in turn serves to the participant coalition interests. The strategic and cooperative coalition game built on this basis describes the development process of the system. Its optimal strategy, which is represented by the Shapley value, provides the compromise strategy of the system balanced technological development. У статті пропонується теоретико-ігровий ресурсний підхід до моделювання процесів сталого розвитку. Вихідна система розглядається як сукупність різних ресурсів і учасників, які споживають і створюють ці ресурси для задоволення їх потреб або інтересів. Учасники системи не діляться на економічні, екологічні та соціальні підсистеми. Їх стратегії або технології спрямовані на отримання доходу від виробництва і споживання ресурсів, що, в свою чергу, спрямовані на коаліційні інтереси учасників. Стратегічна і кооперативна коаліційна гра, побудована на цій основі, описує процес розвитку системи. Її оптимальна стратегія, представлена вектором Шеплі, забезпечує компромісну стратегію збалансованого технологічного розвитку системи. В статье предлагается теоретико-игровой ресурсный подход к моделированию процессов устойчивого развития. Исходная система рассматривается как совокупность различных ресурсов и участников, потребляющих и создающих эти ресурсы для удовлетворения их потребностей или интересов. Участники системы не делятся на экономические, экологические и социальные подсистемы. Их стратегии или технологии направлены на получение дохода от производства и потребления ресурсов, что, в свою очередь, направлены на коалиционные интересы участников. Стратегическая и кооперативная коалиционная игра, построенная на этой основе, описывает процесс развития системы. Ее оптимальная стратегия, представленная вектором Шепли, обеспечивает компромиссную стратегию сбалансированного технологического развития системы.